2020
DOI: 10.1155/2020/7348201
|View full text |Cite
|
Sign up to set email alerts
|

Single-Stage Arthroscopic Anterior and Posterior Cruciate Ligament Repairs and Open Medial Collateral Ligament Repair for Acute Knee Dislocation

Abstract: Till date, there are no clear guidelines regarding the treatment of multiple ligament knee injuries. Ligament repair is advantageous as it preserves proprioception and does not involve grafting. Many studies have reported the use of open repair and reconstruction for multiple ligament knee injuries; however, reports on arthroscopic-combined single-stage anterior cruciate ligament (ACL) and posterior cruciate ligament (PCL) repairs are scarce. In this report, we describe a case of type III knee dislocation (ACL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 17 publications
(21 reference statements)
0
9
0
Order By: Relevance
“…Structural health monitoring technology was first developed in the aerospace field and was originally designed to monitor structural loads. With the development of large-scale complex and intelligent structural design, the content of structural health monitoring is gradually enriched, not only the simple load monitoring, but also the detection of structural damage and the prediction of structural life [ 14 , 15 ].…”
Section: Deep Learning Algorithm Based On Health Monitoringmentioning
confidence: 99%
“…Structural health monitoring technology was first developed in the aerospace field and was originally designed to monitor structural loads. With the development of large-scale complex and intelligent structural design, the content of structural health monitoring is gradually enriched, not only the simple load monitoring, but also the detection of structural damage and the prediction of structural life [ 14 , 15 ].…”
Section: Deep Learning Algorithm Based On Health Monitoringmentioning
confidence: 99%
“…The traditional treatments of multiligament‐injured KD (MLIKD) include conservative treatment, 12 , 13 in situ suture surgery, 14 , 15 , 16 and ligament reconstruction surgery. 17 Although patients who receive operative treatment show better knee function than patients who do not receive operative treatment, 8 , 10 , 18 , 19 it is still unknown which surgical method is best for treating MLIKD.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, two recent case reports reported good outcomes following arthroscopic PCL repair in the MLIK setting with concomitant repairs of the ACL and MCL. 37 Murakimi et al reported that at 2 years after surgery, their patient had a clinically stable knee, and the Lysholm, Knee Injury and Osteoarthritis Outcome Score (KOOS) symptoms, KOOS pain, KOOS activities of daily living, KOOS sport, and KOOS quality of life scores were good, respectively. KT-2000 revealed a mean side-to-side difference of 1.2 mm.…”
Section: Proximal Tearsmentioning
confidence: 99%